Education of Ancient Greece in the Earlier and Later Stages - Lanming, WANG (Social Science Learning Education Journal, 2017)
Education in different countries comes from its different soil. The features of the soil determine the features of its education. This paper respectively discusses the politics, economy, society and culture of Sparta and Athens in the earlier and later stages (the stage of the Hellenistic World). It also compares the aim, institution, content and target of education in the earlier and later stages to approach the research on the education of ancient Greece and the origins of the education of modern Europe and America.